Factors associated with stoma quality of life among stoma patients - Chunli Liao; Ying Qin (Elsevier, 2014)
Background: Quality of life (QOL) concerns in patients with stomas is a globally important health issue. Currently, a lack of understanding into which factors influence QOL post-colostomy hinders the ability of health care professionals to provide appropriate instruction and care needed to improve a patient's QOL. Objectives: To determine the level of stoma-specific QOL and to determine which factors associate with stoma-specific QOL among patients with a stoma. Methods: A convenience sample of 76 patients with stomas was recruited from patients who presented to the ward for checkup in a tertiary hospital in Beijing. Quality of life, self-care, and hope were assessed in patients by the Stoma-QOL, stoma self-care agency scale, and Herth Hope Index, respectively. Statistical analyses were performed using Pearson correlation, t-test, and multiple linear regression analysis. Results: Our stoma-QOL survey demonstrated that stoma patients experienced difficulties functioning in work and social situations, had issues with sexuality and body image, and difficulties with stoma function. Patients expressed concerns related to the stoma itself such as finding privacy to empty the pouch, problems with leakage, and difficulties participating in social activities. Multiple linear regression analysis indicated that self-care agency and hope were the main influencing factors and explained 23.4% of the variance of stoma function and 17.8% of the variance of work/social function. Conclusion: QOL in patients with a stoma was not ideal. Our findings demonstrate that following stoma implantation, improvements in self-care and inspiring hope in patients played an important role in bettering their stoma-QOL. The strength of our study is that we adopted a stoma-specific questionnaire instead of a general scale such as EORTC C30.